Identification of sequence polymorphisms in the D-loop region of mitochondrial DNA as a risk factor for non-Hodgkin lymphoma. (June 2014) - Gao, Yuhuan; Zhao, Guimin; Diao, Lanping; Guo, Zhanjun
Abstract Accumulation of single nucleotide polymorphisms (SNPs) in the displacement loop (D-loop) of mitochondrial DNA (mtDNA) may be associated with an increased cancer risk. We investigated the non-Hodgkin lymphoma (NHL) risk profile of D-loop SNPs in a case–control study. The minor alleles of nucleotides 73A/G, 263A/G, 315C/C insert were associated with a decreased risk for NHL. The minor alleles of the nucleotides 200G/A were specifically associated with the risk of diffuse large B-cell lymphoma, whereas the minor allele of nucleotides 16362C/T and 249Del/A was specifically associated with the decreased risk of T-cell lymphoma. In conclusion, SNPs in mtDNA are potential modifiers of NHL risk. The analysis of genetic polymorphisms in the mitochondrial D-loop can help identify subgroups of patients who are at a high risk of developing NHL.